29 Safety and efficacy of transcatheter aortic valve implantation in nonagenarians with severe symptomatic aortic stenosis. (30th September 2020) - Brennan, PF; Cox, B; Santos, A; Corvan, F; Nzewi, O; Johnston, N; McNeice, A; Jenanathan, R; Owens, C; Spence, MS; Manoharan, G
Abstract : Background: Transcatheter aortic valve implantation (TAVI) is the standard of treatment for high/prohibitive surgical risk patients with symptomatic severe aortic stenosis. Studies reported over the last 5 years have found TAVI to be non-inferior to surgery with respect to intermediate and lower risk patients. In the United Kingdom the number of people living beyond 90 years age continues to rise and this had led to an increasing number of nonagenarians undergoing TAVI for symptomatic aortic stenosis. Outcomes for this group patients are scarcely reported. Purpose: We aimed to report outcomes for all nonagenarians undergoing TAVI in Northern Ireland (NI). Methods: Baseline characteristics, procedural parameters and outcomes were collected using the NICOR database, NI Electronic Care Record and our in-hospital database. We compared all 73 nonagenarians with the remaining 1048 patients that underwent TAVI in NI. Results: Nonagenarians (mean age=91.6 years; female sex 55%) had a lower mean EuroSCORE2 (7.2% vs 8.5%, p=0.03) than the younger group (mean age=81 years; female sex 53%). COPD (4.1% vs. 20.3%, p<0.005), diabetes mellitus (11% vs. 22.3%, p 0.02), prior cardiac surgery (6.8% vs. 19.8%, p0.01) were all significantly lower in the nonagenarian patients. Nonagenarians had significantly more progressive renal dysfunction (mean creatinine clearance 36.4 ml/min vs. 48.3 ml/min, p<0.005). Left ventricular dysfunction (LVEF<50%) was less prevalent in the nonagenarians (14% vs 28%, p 0.01). TAVI was performed under local anaesthetic (LA) in 97% of nonagenarians, compared to 95.5% younger patients, for which 93% vascular access was percutaneous femoral (pTF) (non-nonagenarians LA 98%, pTF 92.2%). Surgical femoral and axillary/subclavian made up the remainder of the access for nonagenarians. Procedural complications for nonagenarians vs the remaining group included stroke (4.3% vs 2.82%, p 0.22), tamponade (1.4% vs 1%, p 0.61) and major vascular injury (1.4% vs 3.4%, p 0.62 ). 30d new pacemaker implantation was similar between the nonagenarian and younger patients (12 vs. 13%, p 0.78). Peri-procedural mortality trended higher in nonagenarians at 4% vs 2%, p 0.20 but, overall, 30d (4% vs. 3%, p 0.47) and 1y (16% vs. 10%, p 0.10) mortality did not significantly differ when compared with the younger patient group. The median survival estimate (figure 1 ) for nonagenarians was 4.9y (IQR 2.3–7.4y) compared to 6.1y (IQR 3.1–9.1y) for the younger patient group (p 0.10).Readmission for heart failure within 1-year was non-significantly lower for nonagenarians (6% vs 10%, p 0.23). Conclusions: In selected nonagenarians we severe symptomatic aortic stenosis, TAVI is both safe and efficacious achieving acceptable short- and long-term outcomes that are comparable with younger patients undergoing TAVI.